Potential of Exserohilum Monoceras as Bioherbicide for Controling Barnyard Grass (Echinochloa Crusgalli) - Sajili, Mohammad Hailmi (2006)
Development of Exserohilum monoceras as a potential bioherbicide for controlling barnyard grass (Echinochloa crus-galli) was investigated in this study. An isolate of indigenous fungus E. monoceras was isolated from diseased Echinochloa crus-galli in Tanjong Karang, Selangor and was evaluated in the laboratory and greenhouse as a potential bioherbicide. This fungus was found to be highly pathogenic to Echinochloa crus-galli seedlings inoculated with 2.1 X lo6 conidialml. The disease symptom appeared 24 h after inoculation as discrete eyespot symptoms with extensive necrosis on the leaves. The lesions did not coalesce, but the leaves and entire plants turned completely necrotic and died. The fungus grew and sporulated well on V8 (half strength) agar with optimum temperature for growth of 30°C. Although most of Exserohilum spp were reported as pathogen to member of Poaceae, but E. mo-eras has a narrow host range, which includes several weedy grasses. Corn, rice and sugarcane showed resistant reaction while dicots were immune. The pathogen penetrated plant surfaces by direct penetration through formation of appressoria randomly on surfaces of E. crus-galli 8 h post inoculation. The appressorium being usually bulbous or cylindrical often ends with the formation of extensive secondary hyphae. The fungus penetrated the cuticle cell wall and grew intra and intercellularly within the tissues. On rice leaves, the fungus grew and penetrated the leaf surface. The fungus did not produce extensive hyphae in rice. The fungus grew on tomato and chili but could not penetrate the cell wall as indicated by lysing of the conidia and germ tubes 8 h post inoculations. The inability of the germinating conidia to penetrate and to progress indicated that tomato and chili are not compatible hosts for this fungus. The level of disease severity on E. crus-galli was linearly related to the conidial concentration of E. monoceras with conidia concentration at lo6 conidia per milliliter resulting in 100% control of the seedlings. Although humidity is the main concern for most mycoherbicides, E. monoceras provided good control of E. crus-galli under mini-plot trials. The fungus reduced competitive ability of E. crus-galli. The results demonstrate the potential of E. monoceras as a bioherbicide to control Echinochloa crus-galli. Additional further research on molecular aspects, mass conidia production, carrier formulation and amendments may further enhance the field efficacy of the pathogen.